Evaluation and Application of Surrounding Rock Stability Based on the Improved Weighting Multidimensional Cloud Model - Jing Long Li; Chao Yuan; Bo Zhang; Bin Sui (Advances in Civil Engineering)
Aiming at the uncertainty in the existing tunnel surrounding rock stability evaluation methods and the inability to make scientific explanations in the process of determining the weights of multiple evaluation indicators, this paper combines subjective weighting based on the nonlinear characteristics of the surrounding rock stability evaluation criteria. Based on the advantages of the method AHP and the objective weighting method CRITIC, a comprehensive weighting method with multiple evaluation indicators is proposed, which is integrated with the multidimensional normal cloud model to establish a surrounding rock stability evaluation method for the improved weighted multidimensional cloud model and accurately obtain the safety level of tunnel surrounding rock construction. The multidimensional cloud model based on improved weighting not only solves the two major problems of randomness and ambiguity in surrounding rock stability evaluation but also fully considers the influence of the information contained in each evaluation factor on the results. The surrounding rock stability evaluation method in this paper is applied to the tunnel construction of the Beijing-Shanghai Expressway and Jinan Expressway connecting line construction project, and the evaluation results have a scientific guiding role for construction risk control.